The "new agricultural collectivism": How cooperatives horizontal coordination drive multi-stakeholders self-organization. Issue 2 (December 2020) - Hannachi, Mourad; Fares, M'hand; Coleno, François; Assens, Christophe
Highlights: Competing French farmers' cooperatives united to control GMO/non-GMO problems. We show that cooperatives coordination can take differing forms. The scale of mutualism has shifted from farmers to competing cooperatives. "New agricultural collectivism" reinforces cooperative bargaining power. Cooperatives unions enabled a multi-stakeholders' dialogue and a self-organization. Abstract: This research studied how stakeholders organize themselves in order to collectively manage the presence or absence of genetically modified organisms (GMOs) at the level of agricultural regions. Using case studies, we show that cooperatives have been able to bundle, coordinate, or influence all stakeholders. We show that these new methods of territorial governance require cooperative relations among cooperatives in direct competition with each other on the market, and a type of "collectivism" on a larger scale. The scale is no longer that of mutualism among farmers but of mutualism among competing cooperatives. This new agricultural collectivism permits cooperatives to reinforce their bargaining power and act as a nexus of relationships between the different stakeholders in the supply chain. This competing cooperatives' unions enabled a multistakeholders' dialogues and a self-organizations of the agricultural production areas.